The Correlations Among Self-Confidence, Learning Motivation, and Speaking Ability of The Eleventh Grade Students Of State Vocational High School 1 of Talang Ubi Pali - Mayangsari; Simaibang, Baginda; Mulyadi (Jurnal Pendidikan Tambusai, 2021)
This thesis is concerned with the inquiry on the correlations among self-confidence, learning motivation, and speaking ability of the eleventh grade students of State Vocational High School 1 of Talang Ubi PALI. The problem of this study is to investigate the correlations among self-confidence, learning motivation, and speaking ability. The total number of the population was 226 students. The sample for this study was 34 students taken through purposive sampling technique. Data were collected by adopting questionnaire for self-confidence and learning motivation, and a test for speaking ability. Data were analyzed by using r-Product Moment and Multiple Regression. The data analysis shows that = 0.516 with = 0,267 and p-value is 0.008. This value is lower than 0.05. This is significant. So, Ha was accepted while Ho was rejected. Conclusions suggest that there are significant correlations among self-confidence, learning motivation, and speaking ability of the eleventh grade students of State Vocational High School 1 of Talang Ubi PALI.